Critical Analysis of the Classical Intelligence Cycle Model in Facing Collaborative Challenges in Indonesia: JEL Classification: H56, H83, D83, O38, H11 - Oktora Aditia; Amy Y. S. Rahayu; Roy Valiant Salomo (Journal of Management and Administration Provision, 2026)
This study presents a critical analysis of the classical intelligence cycle model in addressing collaborative challenges among intelligence agencies in Indonesia. The analysis highlights the limitations of its linear, closed, and hierarchical structure within the context of increasingly complex and multidimensional threat landscapes. Using a qualitative descriptive approach, the study examines barriers to effective collaboration, such as overlapping mandates, lack of integrated information systems, and bureaucratic cultures resistant to openness. Based on interviews, document analysis, and literature review, the study proposes an adaptive and collaborative intelligence framework incorporating elements of intelligence fusion and real-time intelligence cycles. These models emphasize horizontal coordination, digital technology integration, and cross-sectoral partnerships. The research offers strategic recommendations for policy reform, including establishing a national integrated intelligence center, enhancing interagency data interoperability, and promoting collaborative organizational cultures. This study contributes to academic discourse and policy development by advocating for a modern, responsive, and synergistic national intelligence system tailored to Indonesia’s unique institutional and socio-political context.